A study on scientific screening process in a recruitment consultancy firm - SIVANANDAM, DR. PRASANNA; MUDALIAR, MS. POOJA (The journal of contemporary issues in business and government, 2020)
Recruitment is an essential task of every company and applicant screening is one of the main step in the process of recruitment. Whether or not the applicant qualifies is determined by the screening process. In this phase, candidates resume playing a vital role. The main objective of the study is to determine the effectiveness of the screening process in recruitment consultancy firms and to include recommendations for the enhancement of the business and prospective jobseekers to make them eligible for selection. To get the data from the respondents, a structured questionnaire was developed. The questionnaire was circulated to workers working at different consulting firms.